Urethroplasty in Phalloplasty: Surgical Outcomes and Complications a Critical Review - Morgado, Afonso (2017)
Phalloplasty can be either performed as a penile reconstructive or phallic constructive procedure, mainly in penile trauma victims or female-to-male gender reassignment. After the introduction of the radial artery-based forearm free flap and with the further awareness of patient desire to void while standing, urethral reconstruction became a standard procedure and a main goal to attain in phalloplasty. Urethroplasty techniques can be broadly split in two main groups: as part of a tube-within-a-tube skin flap or as an independent other-than-skin graft. Urethral complications, such as fistula, stricture, or stones, are common and often recur after treatment. In this review, the main techniques of urethral reconstruction in phalloplasty are reviewed and compared. Urethral complications are also reviewed as well as their management.